The Assertive (Report and Statement) Speech Act Based on Politeness Strategy in Japanese Companies Communication - Astartia, Dina Dwi (Faculty of Education and Teachers Training, 2023)
Japanese are known to have a very unique work culture. One of the characteristics of Japanese work culture is Hourensou. Hourensou is an important way of how you report to your superiors and colleagues in a Japanese business setting. This study aims to clarify how the practice of assertive (report and statement) speech act in Japanese between superiors to subordinates in the communication frame in Japanese companies. The methods in this study are case study, literature studies, focus group discussion, and interview of 20workers of Japanese Company in Indonesia, with various position from staff to manager. The results show that the practice of the assertive speech act and politeness strategy implemented between superiors to subordinates in Japanese companies. The results also show the similarity and differences between Indonesian and Japanese communication culture at work. The findings of the study have some pedagogical implications,especially to overcome the difficulties and language errors made by Japanese language learners. Beside that, this study also expected as an effort to improve communication skill from graduates of Japanese language education study programs in society, especially into Japanese companies or institutions that use Japanese language as a communication way